The Odd Chromatic Number of a Planar Graph is at Most 8 - Petr, Jan; Portier, Julien (Graphs and combinatorics, 2023)
Petruševski and Škrekovski recently introduced the notion of an odd colouring of a graph: a proper vertex colouring of a graph G is said to be odd if for each non-isolated vertex x ∈ V ( G ) there exists a colour c appearing an odd number of times in its neighbourhood N ( x ). Petruševski and Škrekovski proved that for any planar graph G there is an odd colouring using at most 9 colours and, together with Caro, showed that 8 colours are enough for a significant family of planar graphs. We show that 8 colours suffice for all planar graphs.